Interview notes on mobile money usage in Ghana (The political economy of monetary and financial dependency: West African policy space compared, 2022)
filename: InterviewFintech_Gh_2022.pdf
Keywords: West Africa; Interviews; Fintech; Mobile Money; Ghana